Analisis Kesalahan Fonem Rangkap Mahasiswa Asing di Universitas Negeri Padang - Desti Nurhawinda; Suci Dwinitia; Yulia Pebriani (Signifiѐ, 2024)
This research analyzes the double phoneme errors of foreign students at Universiyas Negeri Padang in the form of deletions, additions and changes to double vowels and double consonants in foreign students at Universitas Negeri Padang. The aim of this research is to describe the forms of double phoneme errors of foreign students at Universitas Negeri Padang.. The type of research used in this research is qualitative research. The method used in this research is the case study method. The research and data sources in the research are Ei Thet Hmo Po (laura) and Win Ei Phyu Tun (Sharon). Data was collected through observation interviews and documentation. Based on the research results, it was found that there were twenty-one data analysis of duplicate phoneme errors of foreign students at Universitas Negeri Padang.